Strategi Komunikasi Fasilitator Pemberdayaan Kementerian PUPR dalam Membangun Kesadaran dan Dukungan Masyarakat Terhadap Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Desa Susukan, Banjarnegara, Jawa Tengah - Utomo, Soleh Wahyu; Aji, Haryo Kusumo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Communication plays a crucial role in human social life, whether in individual, group,or organizational interactions. In the governmental context, communication is key to theeffectiveness of public programs. An example of this is the Self-Help Housing Stimulus Program(BSPS) managed by the Ministry of Public Works and Housing (PUPR). This program involvesField Facilitators (TFL) to ensure effective implementation and communication with thecommunity. Empowerment Facilitators are responsible for educating and empowering thecommunity, as well as ensuring the program's success through direct field support. This studyaims to evaluate the communication strategies used by PUPR empowerment facilitators inbuilding awareness and community support for the BSPS program in Desa Susukan,Banjarnegara, Central Java. The focus is on how these communication strategies affectcommunity understanding and involvement in the self-help housing program. The researchemploys a descriptive qualitative methodology, including interviews, observations, anddocumentation. The findings reveal that the communication strategies of PUPR empowermentfacilitators in the BSPS program in Desa Susukan include four main aspects: disseminatinginformation through WhatsApp groups and direct meetings, motivating the community byexplaining the program's benefits and ensuring adherence to schedules, educating about adequatehousing and program optimization, and providing accurate information on housing standardsaccording to PUPR guidelines. Effective collaboration among the community, village heads, andfacilitators is essential, with the use of effective communication media to ensure information isreceived and understood properly.Keywords: Communication, Empowerment Facilitators, Self-Help Housing